Cyber crime fighters tales from the trenches - Donovan, Felicia (Que Pub., 2009)
Drawing on their experience in law enforcement, the authors take readers behind the scenes, to forensically examine computers, track perpetrators, and tell stories that aren't covered by the media. The text covers the growth of criminal activity on social networks and YouTube, the migration of cybercrime on cellphones, and more.
Includes index. - Print version record
Keywords: Computer crimes; Computer crimes -- Investigation; Internet; Criminalité informatique; Criminalité informatique; Enquêtes; Computer crimes; Investigation